Alzheimer patrimonial: participatory management for the assessment and Memory of the historical heritage tumbesino property. The case (patient) old Cabildo of Tumbes - Bazán Tarrillo, Erick (2019)
This investigation is carried out in the historic center of the city of Tumbes in Peru, which at present houses masonry in a clear state of disrepair, and has as its focus the old Cabildo. In said context, it seeks to discover and analyze the levels of recognition and participatory management, given different uses, of the valuation and memory of this historical cultural heritage, in order to identify the influence they exert in its conservation. The low level of interest of the citizens of Tumbes in the face of the Cabildo’s heritage is equivalent as if society entering a state of oblivion with respect to its monuments, losing even the ability to recognize them, which is analogously defined as heritage Alzheimer.